Nerve conduction velocity in CMT1A: what else can we tell?. (14th July 2016) - Manganelli, F.; Pisciotta, C.; Reilly, M. M.; Tozza, S.; Schenone, A.; Fabrizi, G. M.; Cavallaro, T.; Vita, G.; Padua, L.; Gemignani, F.; Laurà, M.; Hughes, R. A. C.; et al.
Abstract : Background and purpose: Charcot‐Marie‐Tooth disease (CMT) type 1A is characterized by uniformly reduced nerve conduction velocity (NCV) that is fully penetrant since the first years of life, remains fairly stable through the life and does not correlate with disability whereas compound muscular action potential (CMAP) amplitude does. The aim of the present study was to analyze the large amount of electrophysiological data collected in the ascorbic acid trial in Italy and the UK (CMT‐TRIAAL/CMT‐TRAUK) and to use these data to gain insights into the pathophysiology of NCV in CMT1A. Methods: Baseline electrophysiological data from 271 patients were analysed. Electrophysiological recordings were taken from the motor ulnar, median and peroneal nerves and the sensory ulnar nerve. Distal motor latency (DML), motor (MNCV) and sensory (SNCV) nerve conduction velocity, and amplitudes of CMAPs and sensory action potentials were assessed. Electrophysiological findings were correlated with age of patients at examination and the Charcot–Marie−Tooth Examination Score (CMTES). Results: NCV was markedly and uniformly reduced. CMAP amplitudes were overall reduced but more severely in lower limbs. DML decreased and MNCV and SNCV increased with age of the patients, whereas CMAP amplitudes worsened with age and also correlated with CMTES. Conclusions: This is the largest sample of electrophysiological data obtained so far from CMT1A patients. Axonal degeneration as assessed by means of CMAP amplitude reflected clinical impairment and was consistent with a slowly progressive length‐dependent neuropathy. All patients typically had markedly slowed NCV that did, however, slightly increase with age of the patients. The improvement of NCV might depend on myelin thickness remodelling that occurs during the adult life of CMT1A patients.